ENGLISH TO UZBEK SIMULTANEOUS INTERPRETING EXERCISES - Mayusupova Mokhigul Rakhmanovna (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
In light of Uzbekistan's increasingly frequent economic, political, and cultural ties to other nations around the world, there is an ever-increasing need for interpreters. Universities are looking into a variety of interpretation training methods to help students improve their ability to interpret. Since a long time ago, comprehensive training methods for simultaneous interpretation have been desperately needed. The exercises discussed in this article can be used to teach simultaneous translation from Uzbek into English.